2022
DOI: 10.1108/ijoes-05-2022-0105
|View full text |Cite
|
Sign up to set email alerts
|

Does practicing spirituality at workplace make teachers more engaged? Examining the role of emotional intelligence

Abstract: Purpose Drawing on the positive activity model, this study aims to investigate the impact of workplace spirituality on the level of engagement shown by the teachers at higher education institutions. This study also tries to explore if emotional intelligence acts as a mediator in the relationship between workplace spirituality and employee engagement. Design/methodology/approach Using the purposive sampling technique, data were collected from the teachers (N = 287) teaching at various Indian educational insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Recent studies have reported that higher stress is associated with lower level of psychological well-being among the employees (Eden et al, 2020;Salehi et al, 2020). Past research argues that safe workplace environment is important for ensuring flourishing, thriving and engagement at work (Lee, 2022;Pradhan et al, 2022aPradhan et al, , 2022b. Against this context, the present study considers that the level of COVID-19 stress has a bearing upon the psychological well-being of the employees.…”
Section: Work Stress Modelmentioning
confidence: 81%
See 2 more Smart Citations
“…Recent studies have reported that higher stress is associated with lower level of psychological well-being among the employees (Eden et al, 2020;Salehi et al, 2020). Past research argues that safe workplace environment is important for ensuring flourishing, thriving and engagement at work (Lee, 2022;Pradhan et al, 2022aPradhan et al, , 2022b. Against this context, the present study considers that the level of COVID-19 stress has a bearing upon the psychological well-being of the employees.…”
Section: Work Stress Modelmentioning
confidence: 81%
“…Trust acts as a critical factor in individual success and managing organisational change (Tzafrir et al, 2015). Furthermore, a pleasant workplace experience arising out of mutual trust is considered essential for favourable circumstances at work (Pradhan et al, 2022a(Pradhan et al, , 2022b.…”
Section: Trust In Management As a Moderatormentioning
confidence: 99%
See 1 more Smart Citation
“…The findings also validated the second mediating relationship, that is, spiritual leadership alleviates teacher burnout by enhancing teachers' emotional intelligence. Spiritual leadership enables teachers to feel supported by school leaders in their work through organizational behaviors such as vision motivation, caring, and trust in teachers, which in turn enhances teachers' confidence and self−efficacy in accomplishing their teaching tasks [82], helps teachers generate positive affective experiences, and enhances teachers' emotional intelligence [83,84]. Teachers' positive emotions provide continuous motivational support for them to engage in sustainable development education [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although Prati and Karriker (2018) have illuminated a positive relationship between emotional intelligence and employee engagement, the magnitude of this relationship has been variably categorized as weak to moderate. Moreover, the direct effects of emotional intelligence on employee engagement remain underexplored, reinforcing the need for further empirical research, as called upon by Pradhan et al (2023). By concentrating on the ICT sector in Palestine and investigating the relationship between leaders' emotional intelligence and employee engagement levels, this empirical study seeks to overcome these deficiencies.…”
Section: Emotional Intelligence and Employee Engagementmentioning
confidence: 99%